Grenvillian continental collision in South China: new SHRIMP U-Pb zircon results and implications for the configuration of Rodinia - Li, Zheng-Xiang; Kinny, Peter (Geological Society of America, 2002)
The timing of continental collision between the Yangtze and Cathaysia blocks of southChina is an issue that bears on the accretion of Asia, as well as on the assembly and configuration of the Neoproterozoic supercontinent Rodinia. We report in this paper SHRIMP (sensitive high-resolution ion microprobe) evidence that suggests a Grenvillian continental collision in south China, including (1) evidence for 1.3-1.0 Ga metamorphismon both sides of the Sibao orogen between the Yangtze and Cathaysia blocks and (2) sedimentary provenance of possible foreland-basin deposits on the Yangtze side of the orogen that were derived from the Cathaysia block and the Sibao orogen during the continental collision. The occurrence of ca. 1430 Ma granodiorites in southern Cathaysia, along with ca. 1800 Ma basement and Archean protoliths in northern Cathaysia, makes Cathaysia a possible western extension of the Mojave province in southwestern Laurentia. Together with regional data, we suggest that the Sibao orogen could be one of the Grenvillian sutures at the center of Rodinia assembly that brought Australia, Yangtze, and Cathaysia-Laurentia together by ca. 1000 Ma.